PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK DENGAN TEMA KEGIATAN SEHARI-HARI MELALUI MODEL PEMBELAJARAN INSTANT ASSESMENT DENGAN MEDIA CHOOSE NUMBER DI KELAS IV SDN 24 BARUNG-BARUNG BELANTAI - Suryani, Irma (Jurnal Manajemen Pendidikan, 2018)
Based on the acquisition of learning outcomes of Grade IV students of SDN 24 Barung-barung Belantai in thematic learning with the theme of daily activities found that many student learning outcomes are still incomplete. The purpose of this study was to describe and get information about improving student learning outcomes in thematic learning with the theme of daily activities through an instant assessment learning model with the media Choose Number in Class IV SDN 24 Barung-barung Belantai. This research is a classroom action research with research procedures including planning, action, observation and reflection. This study consisted of two cycles with four meetings. Research data was collected using a test sheet. Data is analyzed using percentages. The results of the study and discussion showed that the learning model of Instant Assessment learning model with media Choose Number can improve student learning outcomes in thematic learning with the theme of daily activities in Class IV SDN 24 Barung-barung Belantai. Student learning outcomes in the first cycle were 72.90 increased to 83.87 with an increase of 10.97%.